218k views
5 votes
Help me answer this question please

Help me answer this question please-example-1

2 Answers

3 votes

Answer:

The answer is C.

Explanation:

Just go to Desmos.com and plug it in.

User Jika
by
6.4k points
6 votes

For this case we have:

Let k> 0:

To graph
y = f (x) + k, the graph k units is moved up.

To graph
y = f (x) -k, the graph moves k units down.

Let h> 0:

To graph
y = f (x-h), the graph moves h units to the right.

To graph
y = f (x + h), the graph moves h units to the left.

So, we have:


y = f (x) = \sqrt [3] {x}

Shifted 1 unit down and 4 to the left means:


k = 1\\h = 4


y = f (x) = \sqrt [3] {x + 4} -1

Answer:

Option D

User Cypherfunc
by
5.7k points